2016
DOI: 10.1038/cmi.2015.115
|View full text |Cite
|
Sign up to set email alerts
|

NKT cell subsets as key participants in liver physiology and pathology

Abstract: Natural killer T (NKT) cells are innate-like lymphocytes that generally recognize lipid antigens and are enriched in microvascular compartments of the liver. NKT cells can be activated by self- or microbial-lipid antigens and by signaling through toll-like receptors. Following activation, NKT cells rapidly secrete pro-inflammatory or anti-inflammatory cytokines and chemokines, and thereby determine the milieu for subsequent immunity or tolerance. It is becoming clear that two different subsets of NKT cells—typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 126 publications
(173 reference statements)
3
122
0
Order By: Relevance
“…Diverse NKT cells appear to be more abundant in humans than invariant NKT cells, as shown with CD1d tetramer or dimer staining (Chang et al 2008; Nair et al 2015). In addition to sulfatide and glycosylceramide species, other self and exogenous lipids, including mammalian, bacterial, and pollen-derived phospholipids, have also been identified as antigens for diverse NKT cells as reviewed recently (Macho-Fernandez and Brigl 2015; Bandyopadhyay et al 2016). …”
Section: Diverse Nkt Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diverse NKT cells appear to be more abundant in humans than invariant NKT cells, as shown with CD1d tetramer or dimer staining (Chang et al 2008; Nair et al 2015). In addition to sulfatide and glycosylceramide species, other self and exogenous lipids, including mammalian, bacterial, and pollen-derived phospholipids, have also been identified as antigens for diverse NKT cells as reviewed recently (Macho-Fernandez and Brigl 2015; Bandyopadhyay et al 2016). …”
Section: Diverse Nkt Cellsmentioning
confidence: 99%
“…This protective function of iNKT cells is induced by the stimulation of CD1d-presented host lysophospholipids (Zeissig et al 2012). In liver inflammation, invariant NKT cells were described as pathogenic for chronic injury but potential protective to acute injury (Gao et al 2009; Bandyopadhyay et al 2016). For example, the iNKT-deficient mice develop less alcohol-induced steatosis with reduced neutrophil infiltration (Cui et al 2015).…”
Section: Nkt Cells In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that these lrNK cells have immune memory against specific antigens [39] . + T cell responses [40] .…”
Section: Nk Cellsmentioning
confidence: 99%
“…NKT cells are another type of innate immune cells, which are enriched in the liver and play important roles in the pathogenesis of liver diseases (Bandyopadhyay, Marrero, & Kumar, 2016; Gao, Radaeva, & Park, 2009; Wang, Feng, Park, Yin, & Gao, 2013; Yin et al, 2014). NKT cells recognize lipid antigens presented by CD1d molecules.…”
Section: Potential Targets Of Immune Cells For the Treatment Of Aldmentioning
confidence: 99%